Hopelessness and alcohol use: The mediating role of drinking motives and outcome expectancies - Laura Baines; Andrew Jones; Paul Christiansen (Addictive Behaviors Reports, 2016)
Introduction: Heavy drinking is a considerable public health concern. There is a broad evidence-base examining the separate contributions of personality characteristics, motives and alcohol-expectancies on subsequent alcohol use to identify those at risk. However, little is known about the complex relationships by which these variables may interact to predict drinking behavior. Feelings of hopelessness and anxiety sensitivity are hypothesized to be distal predictors of alcohol use, with outcome expectancies and drinking motives more proximal. Therefore, the aim of the current study was to examine whether hopelessness and anxiety sensitivity influenced alcohol use via drinking to cope and alcohol - outcome expectancies. Methods: We recruited 230 participants to complete an online questionnaire consisting of the brief drinking motives questionnaire, the Substance Use Risk Profile scale and Brief Comprehensive Effects of Alcohol scale. We conducted path analyses using structural equation modelling. Results: We demonstrated a significant direct effect of anxiety sensitivity on alcohol use, and a significant serial indirect effect of hopelessness through coping motives and alcohol outcome expectancies. Conclusions: These findings suggest feelings of hopelessness may predict alcohol consumption through a complex pathway and future research should use these findings to identify individuals at risk of increased alcohol use.